The mental health of refugee children and teenagers and its consequences in the genesis of the resignation syndrome (Research, Society and Development, 2022)
This research aimed to investigate the impact of migratory flows on the mental health of refugee children and adolescents, as well as to verify the impact of these mental changes in the genesis of the resignation syndrome. For this, an integrative literature review was used in the electronic databases: LILACS, SciELO, Frontiers and in the FIDES-UFRN journal. The following descriptors were used: “Refugees”, “Mental Health”, “Child”, “Syndrome” and “Coma”. The boolean operator “AND” was used. Articles available in full were included; published between 2016 and 2021; in Portuguese, English or Spanish; whose titles and abstracts were in line with the purpose of this study. Theses, dissertations and proceedings abstracts were excluded. Subsequently, data collection, critical analysis and synthesis were carried out. The resignation syndrome is a still obscure and poorly detailed pathology, regarding its etiology and pathophysiology involved. It is also inferred that studies aimed at analyzing the mental health of refugee children are still scarce, but the data point to the direct existence of psychic suffering in this age group, which is related to the emergence of the aforementioned syndrome. Based on the data collected, it is concluded that psychic suffering occurs in children who experience involuntary migration. The repercussions of this process on the mental health of refugee children, illustrated by the resignation syndrome, reveal the magnitude of mental suffering triggered by strenuous and lengthy migrations, marked by violence and intolerance, which constitute a public health problem.